2022
DOI: 10.1002/rcr2.938
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 mRNA vaccine‐related interstitial lung disease: Two case reports and literature review

Abstract: The Pfizer‐BioNTech mRNA vaccine (BNT162b2) is an effective and well‐tolerated coronavirus disease 2019 (COVID‐19) vaccine. However, rare adverse events have been reported. We report two cases of COVID‐19 mRNA vaccine‐related interstitial lung disease (ILD). A 67‐year‐old man and a 70‐year‐old man with underlying ILD presented to our hospital with a few days of fever and respiratory symptoms after receiving the BNT162b2 vaccine. Drug‐related pneumonitis due to the COVID‐19 mRNA vaccine was diagnosed. One case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(33 reference statements)
1
12
2
Order By: Relevance
“… 12 This patient shared similar features with the eight patients who developed lung injury post COVID-19 vaccination and responded favorably to steroids. 3 , 12 , 16 - 18 A past SARS-CoV-2 infection may have evoked a vigorous immune response after vaccination, resulting in respiratory distress syndrome in our patient. Hence, it is also plausible that this patient's diagnosis was purely fortuitous.…”
Section: Discussionmentioning
confidence: 77%
“… 12 This patient shared similar features with the eight patients who developed lung injury post COVID-19 vaccination and responded favorably to steroids. 3 , 12 , 16 - 18 A past SARS-CoV-2 infection may have evoked a vigorous immune response after vaccination, resulting in respiratory distress syndrome in our patient. Hence, it is also plausible that this patient's diagnosis was purely fortuitous.…”
Section: Discussionmentioning
confidence: 77%
“…With the increase in the administration of SARS-CoV-2 vaccines worldwide, several adverse reactions have been reported. Vaccination-induced pneumonitis seems to be rare, and to the best of our knowledge, only five cases have been reported so far ( Table 1 ) ( Yoshifuji et al, 2022 , Park et al, 2022 , Farooq et al, 2022 , So et al, 2022 ). In three cases, pneumonitis appeared within a few days after administration of the second dose, and patients experienced fever, cough, and dyspnea.…”
Section: Discussion and Literature Reviewmentioning
confidence: 92%
“…Accumulated case reports have revealed several adverse effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. Although thrombocytopenia is relatively common, vaccination-induced pneumonitis is rare, with only five cases reported to date ( Yoshifuji et al, 2022 , Park et al, 2022 , Farooq et al, 2022 , So et al, 2022 ). Here we report the case of a patient who developed thrombocytopenia and pneumonitis concurrently after receiving a SARS-CoV-2 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…To date, case-based information has been accumulated, starting with the first case report of vaccine-related ILD induced by an mRNA vaccine [ 174 ]. These cases have consistently shown that ILD occurred within 1-10 days after the first or second shot of the vaccine and sometimes improved spontaneously [ 175 , 176 , 177 ] but sometimes was accompanied by respiratory failure and treated with corticosteroid (methylprednisolone 0.5-1mg/kg and/or pulse therapy) [ 177 , 178 , 179 , 180 , 181 , 182 ]. The major radiological findings are GGO and consolidation represented by an HP or OP pattern [ 175 , 181 ].…”
Section: Ild Induced By Mrna Vaccine For Sars-cov-2mentioning
confidence: 99%
“…These cases have consistently shown that ILD occurred within 1-10 days after the first or second shot of the vaccine and sometimes improved spontaneously [ 175 , 176 , 177 ] but sometimes was accompanied by respiratory failure and treated with corticosteroid (methylprednisolone 0.5-1mg/kg and/or pulse therapy) [ 177 , 178 , 179 , 180 , 181 , 182 ]. The major radiological findings are GGO and consolidation represented by an HP or OP pattern [ 175 , 181 ]. Histopathological lymphocytic alveolitis, or OP, was proven in some of these cases [ 181 , 182 ].…”
Section: Ild Induced By Mrna Vaccine For Sars-cov-2mentioning
confidence: 99%